Malignant Melanoma Presenting as Thoracic Midline Malignancy: Clinicopathologic and Molecular Features. Issue 1 (January 2018) - Yao, Keluo; Zhao, Weiqiang; Bajestani, Saeed; Gru, Alejandro; Otterson, Gregory; Shilo, Konstantin
Abstract : Because of rarity, clinicopathologic and genomic profiles of noncutaneous malignant melanoma (MM) are not well characterized. In this study, we provide a detailed evaluation of 6 cases of MM presenting as thoracic midline malignancy. The tumors occurred in 6 white patients (5 males and 1 female; medium age, 71.5 y; range, 55 to 81 y). At presentation, the disease was confined to the chest (6/6) with 4 cases subsequently showing brain metastasis. All 6 tumors featured epithelioid and 1 case also spindle cell morphology. Three of 6 tumors had melanin and all 6 expressed melanocytic markers. Molecular characterization showed 2 of 6 tumors with BRAF "hot spot" genetic alterations (both with BRAF V600K) and 1 with NF1 mutation. All 6 patients died of the disease within 1 year (mean survival, 4.8 mo). One patient showed a partial response to BRAF inhibitor. Our study shows that MM in this location has a spectrum of genetic alterations. The findings highlight the need for comprehensive next generation sequencing-based molecular testing to optimize targeted therapies of this aggressive malignancy.